Implementation of The Journalistic Ethics Code in Reporting The Russian Invasion of Ukraine on CNNIndonesia.com - Kartinawati, Erwin; Prabuadi Kencana, Dhimas (Program Studi Komunikasi dan Penyiaran Islan STAIMAS Wonogiri, 2024)
Online media is now the most widely consumed media by the public regarding its speed. Online media prioritizes speed. However, the pursuit of speed sometimes causes news in online media to not comply with the journalistic code of ethics, especially regarding accuracy, balance, and objectivity, when presenting a fact or information. Implementing a code of ethics for journalistic processes and products is essential so that the public gets correct information, is not biased, and is free from interests and prejudices. Implementing a journalistic code of ethics is vital concerning the power of the media in influencing public opinion and behavior. This study aimed to determine the implementation of the journalistic code of ethics regarding reporting on the Russian invasion of Ukraine on CNNIndonesia.com. The data analyzed were the news presented in the 17 February to 3 March 2022 editions. The data processing stage involved evaluating news samples and then conducting a reliability test by two coders. The assessment results were then recorded in a table to be described descriptively. The research found that not all of the news presented by CNNIndonesia.com about the Russian invasion of Ukraine complies with the journalistic code of ethics. There were still some news stories that added journalists' personal opinions or opinions; only showing sources as one party in the news involving two parties; and there are still errors in writing words, names of sources, names of cities, and names of countries.